Параметарска анализа на пожарна отпорност на различни типови армиранобетонски плочи - Салиху, Фидан (Градежен факултет, УКИМ, Скопје, 2020)
Reinforced concrete slabs are widely used buildings elements. Floor slabs, as horizontal structural elements, have a very important role in providing bearing capacity, usability and stability of the building as a whole. Their proper selection and design, when they are exposed to different types of loads (permanent, variable and incidental), should provide stable and safe structure during the exploitation period. The fire resistance of building members is an important part of any structural and fire safety design. In case of fire floor slabs do not have only load bearing function. In most cases they are used as elements for separating the fire compartment. Where compartmentation is required, the elements forming the boundaries of the fire compartment, including joints, shall be designed and constructed in such a way that they maintain their separating function during the relevant fire exposure. This shall ensure, where relevant, that integrity failure does not occur, insulation failure does not occur, thermal radiation from the unexposed side is limited. Does the floor structure meet the required fire resistance criteria mainly depends on: mechanical and thermal characteristics of the materials used for the construction; support conditions; concrete cover thickness; slab thickness; steel ratio and fire scenario. In order to obtain a more realistic picture of the behavior of reinforced concrete slabs in fire, a number of parameters that are not incorporated in previous research are included in the analyses conducted within the doctoral dissertation. This research presents the numerically achieved results for the fire resistance of one way and two way reinforced concrete slabs with different spans, different concrete cover thickness, different reinforcement scheme and fire scenarios. For that purpose, the computer program SAFIR2016 is used. For the one way slabs, 2D and 3D Analyses are conducted. In case of 2D Analyses, the slabs are discretized with beam elements, and in case of 3D Analyses shell elements are used. The 3D analyses of one way slabs are performed for 1 m strips and for the real width of the slabs. For the two way slabs, 3D-Analyses are conducted for the real width od the slabs and for that purpose only shell elements are used. For comparison, the slabs are analyzed by using the simplified method given in EN 1992-1-2. In order to increase the fire resistance of reinforced concrete slabs, based on the performed parametric analyzes, conclusions are drawn and recommendations for the proper design of the reinforced concrete slabs are given.
Докторска дисертација одбранета во 2020 година на Градежниот факултет во Скопје, под менторство на проф. д–р Мери Цветковска.
Keywords: RC slab, fire resistance, 2D and 3D analyses, SAFIR